Faktor Predisposisi yang Berhubungan dengan Kunjungan K4 Ibu Hamil di Unit Pelaksana Teknis Daerah Puskesmas Dawan I Klungkung - Ni Kadek Dwi Pradnyawati; Ni Made Dwi Mahayati; Ni Wayan Suarniti (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2023)
The high MMR in Indonesia proves that efforts to reduce MMR are not optimal, one of which is antenatal care (ANC). ANC services can be assessed from the achievement of the fourth visit (K4). The purpose of the study was to determine the predisposing factors associated with K4 visits by pregnant women at UPTD. Health Center Dawan I Klungkung. This type of research is an analytic survey with a cross sectional approach. Implementation March - April 2022. Sampling with a proportional sampling totaled 54 respondents. The research instrument used a questionnaire and the ANC register book. Univariate data analysis and statistical analysis with a significance level of p 0.05. The results of the univariate analysis were pregnant women aged 20-35 years (72.2%), secondary education (57.4%), maternal parity (70.4%), pregnancy interval 24 months (76.3%), high knowledge (72.2%), positive attitude (79.9%) and K4 visits (63.0%). The results of bivariate analysis using the chi square test on the characteristics of age (p = 0.003), education (P0,05), parity (p0,05), pregnancy interval (p= 0.007), knowledge (p= 0.030), attitude (p= 0.036 ). The conclusion of this study is that there is a relationship between age, education, parity, pregnancy distance, mother's knowledge and attitude towards K4 visits for pregnant women at the Regional Technical Implementation Unit. Pregnant women are expected to carry out K4 pregnancy checks according to standards.